Dynamic Routing of Voice Traffic in Corporate IP networks - Соловьев, А. В.; Майструк, Д. В.; Бондаренко, В. Н. (Problems of Informatization and Control, 2013)
Extant routing protocols of voice and IP traffic are analyzed. Requirements for the development ofvoice traffic routing protocol in corporate IP networks are formulated.